Spinel manganites synthesized by combustion method: Structural characterization and catalytic activity in the oxidative degradation of organic pollutants - Diez, Alejandra Silvina (2017)
Two spinel-type oxides, CuMn2O4 and CoMn2O4 were synthesized by a simple combustion method. The oxides were characterized by X-ray Diffraction, infrared spectroscopy, scanning electron microscopy and atomic absorption spectroscopy. The structures of the obtained oxides were refined by the Rietveld method. The obtained samples were tested in the catalytic degradation of phenol and methyl orange. Two different oxidants were employed: potassium persulfate and peroxymonosulfate. The catalytic activity was tested, as well as the degradation efficiencies. The best results were obtained with the copper substituted oxides, using oxone as oxidant. With this system, mineralization of total organic carbon (TOC) reached more than 94% within 120 min of reaction. For cobalt mixed oxides, the TOC mineralization reached as much as 68% in the same condition. The activation mechanisms for the different systems studied in this work are discussed and two different pathways are proposed depending on the oxidant and/or the substitution metal.